2015
DOI: 10.1016/j.trf.2015.04.009
|View full text |Cite
|
Sign up to set email alerts
|

Method of transportation and drinking among club patrons

Abstract: Objective The current study examines the variation in alcohol use among nightclub patrons under three transportation conditions: those who departed from a club using modes of transportation other than cars or motorcycles (e.g., pedestrians, bicyclists, subway riders); those who were passengers of drivers (auto/taxi passenger patrons); and those who drove from the club (driving patrons). We seek to determine whether patrons' choice for how to leave the club contributes to their risk, as assessed by blood alcoho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…These are similar to reasons reported by drivers and passengers in private passenger vehicles (e.g., Begg & Langley, 2000). In addition, intoxicated persons may employ taxi cabs or rideshare vehicles as a safer alternative to driving (Bourdeau, Miller, Johnson, & Voas, 2015), and intoxication is related to lower seat belt use (Foss, Beirness, & Sprattler, 1994;Li, Kim, & Nitz, 1999). However, it is not known why rear seat belt use in taxis is significantly less than in private passenger vehicles, and further research is warranted.…”
Section: Discussionsupporting
confidence: 71%
“…These are similar to reasons reported by drivers and passengers in private passenger vehicles (e.g., Begg & Langley, 2000). In addition, intoxicated persons may employ taxi cabs or rideshare vehicles as a safer alternative to driving (Bourdeau, Miller, Johnson, & Voas, 2015), and intoxication is related to lower seat belt use (Foss, Beirness, & Sprattler, 1994;Li, Kim, & Nitz, 1999). However, it is not known why rear seat belt use in taxis is significantly less than in private passenger vehicles, and further research is warranted.…”
Section: Discussionsupporting
confidence: 71%
“…Our task presented a choice between driving oneself and paying for a ride service, but other alternatives (e.g. selecting a designated driver) may involve distinct decision‐making strategies [21]. Our task presented trade‐offs within a set range (one to six drinks, $5–$25), and individuals might alter their decision strategy at different levels of each (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…With respect to evidence of increased drinking by AT users, some articles indicated that those who increased their alcohol consumption were already classified as heavy drinkers or people who typically engage in risky behaviors ( Shoreet al, 1991 , Barr and MacKinnon, 1998 , Caudill et al, 2000 , Caudill et al, 2001 , Hardinget al, 2001 , Grube and Nygaard, 2009 , Family Sues Over Safe-Ride Program, 2004 ). Other studies also noted that those who use safe ride programs or designated drivers were likely to have higher BAC’s generally or were more likely to have a few more drinks because they were not driving ( Chan, 2011 , Sykeset al, 2014 , Bourdeau et al, 2015 , National Academy of Sciences, Engineering, and Math (NASEM), 2018 ). None of the articles reporting an increase in the number of drinks consumed when participants used AT reported any adverse harms in this behavior (e.g., no increase in assaults or other alcohol-related crime).…”
Section: Resultsmentioning
confidence: 99%